Improvement in Depression Scores After 1 Hour of Light Therapy Treatment in Patients With Seasonal Affective Disorder - Reeves, Gloria M. (J Nerv Ment Dis, 2012)
The purpose of this study was to investigate possible rapid effects of light therapy on depressed mood in patients with seasonal affective disorder. Participants received 1 hour of bright light therapy and 1 hour of placebo dim red light in a randomized order crossover design. Depressed mood was measured at baseline and after each hour of light treatment using two self-report depression scales (Profile of Mood States–Depression-Dejection [POMS-D] subscale and the Beck Depression Inventory II [BDI-II]). When light effects were grouped for the two sessions, there was significantly greater reduction in self-report depression scores by −1.3 (p = 0.02) on the BDI-II and −1.2 (p = 0.02) on the POMS-D. A significant but modest improvement was detected after a single active light session. This is the first study, to our knowledge, to document an immediate improvement with light treatment using a placebo-controlled design with a clinical sample of depressed individuals.